The treatment of rheumatoid arthritis using Chinese medicinal plants: From pharmacology to potential molecular mechanisms. (24th December 2015) - Lü, Shaowa; Wang, Qiushi; Li, Guoyu; Sun, Shuang; Guo, Yuyan; Kuang, Haixue
Abstract: Ethnopharmacological relevance: Rheumatoid arthritis (RA) is a common worldwide public health problem. Traditional Chinese Medicine (TCM) achieved some results to some extent in the treatment of rheumatoid arthritis (RA). Especially in China, TCM formulas are used in the clinic because of their advantages. Some of these TCM formulas have been used for thousands of years in ancient China, they pays much attention to strengthening healthy qi, cleaning heat, and wet, activating blood, etc. So TCM in anti-RA drug is considered as a simple and effective method. In addition, TCM are also traditionally used as extracts and many Chinese herbs which are considered to be effective for RA. With the advancement of technologies and research methods, researchers have devoted themselves to exploring new therapeutic materials from troves of TCM. The components of TCM are identified and purified, which include alkaloids, coumarins, flavonoids, saponins and so on. However, little or no review works are found in the research literature on the anti-RA drugs from TCM. The present review aims to provide systematically reorganized information on the ethnopharmacology, phytochemistry and pharmacology of TCM used traditionally against RA. The information recorded in this review will provide new directions for researchers in the future. Materials and methods: Relevant scientific literatures were collected from Chinese traditional books and Chinese Pharmacopoeia. Several important pharmacology data, clinical observations, animal experiments on effects of anti-RA drugs from TCM and their mechanisms were extracted from a library and electric search (Pubmed, PubChem Compound, Science Direct, Spring Link, Elsevier, Web of Science, CNKI, Wan Fang, Bai du, The Plant List, etc.). We collected information published between 2002 and 2015 on Chinese medicine in the treatment of RA. Information was also acquired from local classic herbal literature, conference papers, government reports, and PhD and MSc dissertations. Results: This review mainly introduces the current research on anti-RA TCM formulas, extracts and compounds from TCM, pharmacological data and potential mechanisms (inhibit osteoclast proliferation, suppress fibroblast-like synoviocytes (FLSs) growth, decrease the expression of inflammatory cytokines, blocking signal pathways, etc.). Conclusions: TCM, as a multi-component and multi-target approach, which is a perfect match with the holistic concept of systems biology, is applicable in the treatment of RA. The synergistic connections of Chinese herbs and mechanisms of related active compounds on RA increase the trust for TCM. TCM as alternative remedies for RA not only has an important position in the world market, but also has an irreplaceable role in the treatment of RA in future. Graphical abstract: